2015
DOI: 10.1007/s10792-015-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined pars plana vitrectomy–scleral buckle versus pars plana vitrectomy for proliferative vitreoretinopathy

Abstract: The purpose of the study is to evaluate the surgical outcomes of combined pars plana vitrectomy-scleral buckle (PPV-SB) versus pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment complicated with proliferative vitreoretinopathy (PVR). One thousand one hundred and seventy four patients with rhegmatogenous retinal detachment surgery between January 2002 and December 2013 were retrospectively reviewed. Patients with grade C PVR treated with either combined PPV-SB or PPV alone were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…The current treatment of RD associated with PVR is vitrectomy [1], [7], [8], [9], [10], [11], [12], [13], [14]. Several surgical techniques and use of surgical adjuvant drugs were described for the treatment of PVR [7], [8], [9], [10], [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current treatment of RD associated with PVR is vitrectomy [1], [7], [8], [9], [10], [11], [12], [13], [14]. Several surgical techniques and use of surgical adjuvant drugs were described for the treatment of PVR [7], [8], [9], [10], [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The current treatment of RD associated with PVR is vitrectomy [1], [7], [8], [9], [10], [11], [12], [13], [14]. Several surgical techniques and use of surgical adjuvant drugs were described for the treatment of PVR [7], [8], [9], [10], [11], [12], [13], [14]. Adding scleral buckle, performing membrane peeling, using retinotomy-retinectomy techniques, using heavy perfluorocarbon liquids and advanced tamponades such as silicone oil/perfluorocarbon gases are the introduced advances in surgery [7], [8], [9], [10], [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has indicated that RPE cells are strongly associated with the progression of PVR [ 20 , 21 ]. Accompanied by the breaking of retinal integrity, RPE cells are exposed to the vitreous which is rich of growth factors/cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, proliferation and migration of RPE cells has an essential role in the progression of proliferative vitreoretinopathy (PVR) and other fibro-proliferative eye diseases ( 21 , 22 ). Evidence has indicated that viability of RPE cells is associated with various ophthalmic diseases through regulation of EMT molecular markers ( 22 ). Research has also demonstrated that RPE cell apoptosis is influenced by a combination of macrophages and soluble mediators in the progression of AMD ( 11 ).…”
Section: Discussionmentioning
confidence: 99%